PENGARUH MINAT DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA DI SMK KETINTANG SURABAYA - MARGINING RAHAYU (Jurnal Pendidikan Akuntansi (JPAK), 2013)
In education, learning is a changing process of human behaviour for the better. In school environment, the changes can be seen through learning outcomes, where the implementation to achieve the learning outcomes are influenced by various factors such as interest and motivation to learn. The purpose of this study were to determine whether the interest and motivation to learn it partial effect and simultaneously affect on student learning outcomes in accounting subjects in class X program accounting expertise SMK Ketintang Surabaya. This research is a quantitative research. The population of this study were all tenth grade students in vocational programs accounting expertise Ketintang Surabaya as many as 247 students. Sample was 143 respondents drawn with proportional random sampling technique. The data collection were using documentation and questionnaires. Analysis of the data using multiple regression analysis. According to the analisis data, it can be concluded that interest and learning motivation partially and simultaneously influence significant toward student’s learning outcomes. Key words: Interest, learning motivation, outcomes of learning